EFEKTIVITAS MODEL SINEKTIK BERORIENTASI BERPIKIR KRITIS DALAM MENINGKATKAN KEMAMPUAN APRESIASI KARAKTER TOKOH PADA NOVEL REMAJA 24 HOUR STAY AT SCHOOL KARYA ESA KHAIRINA HUSEIN: Studi Eksperimen pada Siswa Kelas VIII SMP N 3 Pangalengan Kabupaten Bandung Tahun Ajaran 2012/2013 - Sumiati, Ayi (2013)
This study entitled "Effectiveness sinektik oriented models of critical thinking in improving appreciation of the novel character of the 24-hour stay at school work Khairinahuseinesa" (Experimental Study in Class VIII SMP Pangalengan Bandung District 3 Academic Year 2012/2013). This research is motivated by the following. First, teachers are required keprofesionalnya in choosing the right model for students to learn actively, fun, and achieve optimal learning outcomes. Secondly, the teaching of literature can help education as a whole if the scope includes four benefits, namely: helping skills, increase cultural knowledge, developing creativity and flavors, as well as support the formation of character. As for the purpose, namely: 1) to describe the intrinsic elements contained in the novel; 2). Mendeskrisikansinektik application of the model in the appreciation of the character of the novel; 3). Endeskripsikan models sinektik effective appreciation of the character in the novel; 4). Describe the results of analysis students to the values of the character of the novel; 5). describe students' responses to the model sinektik in appreciation of the character. The method used is descriptive method of analysis and experimentation. Descriptive method is done by describing the facts of which was then followed by analysis. While the experimental method using a randomized pretest-design PotestThe Control Group Design. The second group was given the test, both the initial test and final test. Class control group not given the treatment while the experimental class was given treatment. Based on these results, the authors obtained the following findings: 1) there is an intrinsic element of which is owned by the novel such as theme, plot, setting, character and characterization, point of view, style, and mandate; 2) there are differences in pre-test and post-test results in the experimental class, which is obtained t count: 22.143 with n: 30, with a significance level α: 0.05 and tables contained in 2,048 t. There are differences in post-test results in the experimental class and the control class that is obtained t count: 11 043 with n: t 30 Table: 0.05 and t table: 2,048, mean t count> t table or 11 043> 2,048; 3) there is a character based on the value of analysis contained in the novel students are religious, disciplined, independent, friendly, responsibility, and love to read; 4) the response of students to the model sinektik interesting, exciting, foster creativity, increase motivation to learn, and able to analogous. The conclusion is that the model used sinektik effective in improving the ability of appreciation of the character and foster students' creativity.